Bio-concentration of hazardous metals in migrant shorebirds in a key conservation reserve and adjoining areas on the west coast of India - K.M. Aarif; K.A. Rubeena; Aymen Nefla; Zuzana Musilova; Petr Musil; Sabir Bin Muzaffar (Ecotoxicology and Environmental Safety)
Heavy metal pollution is a growing environmental concern as it causes the degradation of wetlands by affecting the organisms at different trophic levels. Shorebirds typically feed on benthic invertebrates including polychaete worms, crustaceans and molluscs. Thus, the assessment of bioconcentration of heavy metals in shorebirds provides an insight into the extent of bioaccumulation of these hazardous metals in the upper trophic levels. We studied the variation in the bioconcentration of hazardous heavy metals (chromium, lead and cadmium) in the faeces of 12 species of shorebirds (belonging to different foraging guilds including Endangered Great Knot, Vulnerable Grey Plover, Broad billed Sandpiper and Curlew Sandpiper and Near Threatened Eurasian Oystercatcher, Ruddy Turnstone and Dunlin) in relation to trends in their abundance over a period of five years (2019–2023). The study spanned over three different habitats (mudflats, mangroves and sand beaches) of Kadalundi Vallikkunnu Community Reserve (KVCR) and adjoining sand beaches, which are important wintering/ stop-over sites for the migrant shorebirds that provide abundant nutritional resources for the foraging shorebirds. We demonstrate that there has been a drastic increase in the heavy metal concentration in shorebird faeces from 2019 to 2023. Further, the findings indicate that predating and biofilm-grazing shorebirds in mangrove habitats, as well as small-bodied shorebirds in general are exposed to high levels of heavy metals. This study highlights that heavy metals in the coastal habitats are increasing and that there are potential risks from exposure to foraging shorebirds. Heavy metals have known adverse effects on shorebirds. Our study shows that reducing pollution and protecting community reserves alongside their surrounding habitats are crucial to combat biodiversity loss and maintain diversity in these areas.